Clinical Research of Obstructive Sleep Apnea and Acute Coronary Syndrome: Current Status and Future Direction - ZHANG Ming, WANG Wenjuan, HAO Wen, CHEN Jibin, XIA Wei, SHAO Yibing, WANG Bin (Zhongguo quanke yixue, 2025)
Obstructive sleep apnea (OSA) is one of the most common sleep disorders, which is closely related to a variety of cardiovascular diseases, and has become one of the key directions for the control and prevention of cardiovascular disease risk factors. In recent years, many clinical studies have confirmed that OSA is closely related to the initiation and evolution of acute coronary syndrome (ACS). Therefore, this article summarized the status quo of clinical studies on OSA and ACS, the shortcomings of current studies, and prospects for future research directions.